2022
DOI: 10.1093/eurjcn/zvac006
|View full text |Cite
|
Sign up to set email alerts
|

Remote-delivered cardiac rehabilitation during COVID-19: a prospective cohort comparison of health-related quality of life outcomes and patient experiences

Abstract: Aims Enforced suspension and reduction of in-person cardiac rehabilitation (CR) services during the coronavirus disease-19 (COVID-19) pandemic restrictions required rapid implementation of remote delivery methods, thus enabling a cohort comparison of in-person vs. remote-delivered CR participants. This study aimed to examine the health-related quality of life (HRQL) outcomes and patient experiences comparing these delivery modes. Methods and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…In keeping with findings by Candelaria et al and Huang et al, 29 30 our study showed that CR DHIs can significantly improve health related quality of life and anxiety and depression at EOP, with the majority of these changes being sustained at 6-month follow-up. These improvements can be attributed to the strong emphasis placed on addressing psychosocial health through group-based activities, stress management and psychological support.…”
Section: Discussionsupporting
confidence: 92%
“…In keeping with findings by Candelaria et al and Huang et al, 29 30 our study showed that CR DHIs can significantly improve health related quality of life and anxiety and depression at EOP, with the majority of these changes being sustained at 6-month follow-up. These improvements can be attributed to the strong emphasis placed on addressing psychosocial health through group-based activities, stress management and psychological support.…”
Section: Discussionsupporting
confidence: 92%
“…12 Our findings also echo the international body of literature showing that HRQoL improvements for people with HF engaging in home-based CR are similar to those participating in centrebased provision. 12,28 That the magnitude of improvement in total MLHF scores was not only statistically significant but also clinically meaningful, with a ≥5 point improvement in almost two-thirds of participants.…”
Section: Discussionmentioning
confidence: 96%
“…It is important that these results are interpreted with caution, given that the effects of the COVID pandemic impacted patient willingness and preparedness to participate in the remote model of CR delivery. Remote methods of CR delivery may have been more appealing to those who were already self-motivated to exercise, whereas in-person sessions were preferred by patients who needed more support because of closer and direct instruction, guidance, and supervision 24. This proposition is supported by a study that examined motivation in patients participating in cardiac telerehabilitation versus traditional CR, which found that the traditional CR group was more likely to be dependent on external sources of motivation, such as health personnel, compared with the telerehabilitation group 47…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a secondary analysis of data from a larger study of patient outcomes from CR, 24 which used a prospective observational design. Human Research Ethics and Research Governance Committee approval for all participating sites has been granted for this study (HREC Ref.…”
Section: Methodsmentioning
confidence: 99%